Analisis Pengembangan Usaha Pada CV. Zam Zam Collection Kabupaten Jombang - Nasikhatu Rosalina; Lailatus Sa’adah; Ita Rahmawati (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2020)
This study aims to find out how the business description of CV. Zam-Zam Collection so far and the possibility of developing the hijab business are seen from the financial aspect. The data obtained from this study are quantitative data in the form of primary data obtained through direct observation and interviews with respondents (the owner of CV. Zam-Zam Collection) using structured interview text that has been prepared. While secondary data are obtained from literature studies, reports, and other literature relating to this research as well as institutions or agencies involved in research such as the statistical body of the statistics. This research tool is Microsoft Excel. Technical analysis of the data used is investment analysis which from the calculation gets the following results: Payback Period shows that the Payback Period is 3 years 8 days. The Average Rate of Return shows that the Average Profit level is 2,14%. Net Present Value obtained a positive value of Rp. 64,047,828. From the Internal Rate of Return method, an interest rate of 27,4% is greater than the specified interest rate of 20%. While the Profitability Index method shows the results obtained greater than 1 which is equal to 1,21. From the calculation of these five methods, it can be said that the business of CV. Zam-Zam Collection is feasible to be developed.